22q11.2q13 duplication including SOX10 causes sex‐reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. Issue 4 (22nd March 2017) - Falah, Nadia; Posey, Jennifer E.; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R.; Harel, Tamar
Abstract : Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149–151], of an individual with 22q duplication and sex‐reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10 . Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.